One‐pot preparation of small lipid‐indocyanine green nanoparticles to induced intracellular oxidative/thermal stress damage for effective colorectal cancer therapy - Zhibin Bi (Wiley, 2021)
Abstract In the current study, a one‐pot method to prepare small lipid‐indocyanine green (ICG) nanoparticles (L‐ICG NPs) is proposed for the treatment of colorectal cancer. The L‐ICG NPs showed size distribution at around 20 nm with high stability and biocompatibility. In addition, they can respond to light irradiations to exert oxidative/thermal stress damage, which showed effective anticancer benefits in vitro and in vivo using HT‐29 cells as the model.